Martial arts and dualistic philosophy: conflict, harmony and the search for balance - Fanghui Li; Liang Fu (Trans/Form/Ação)
This paper focuses on how the reconstruction of moral self and spiritual freedom can be realized through the philosophical analysis of dialectical unity in martial arts practice. It examines how Eastern philosophies, such as Taoism, Buddhism and Confucianism, inform martial arts, emphasizing the integration of opposing forces like mind and body, strength and softness, and offense and defense. By articulating a central claim that martial arts serve as embodied vehicles for ethical transformation, this paper contributes to contemporary debates in virtue ethics and philosophy of mind. It argues that martial arts, particularly Wushu, embody a practical philosophy based on the body’s phenomenology, grounded in the dynamic structure of Yin and Yang. This embodied dialectic fosters virtue by integrating affective, physical and cognitive dimensions of self-cultivation. Engaging with Western subjectivity traditions and modern body theory, the paper explores how martial arts transcend dichotomies, offering a holistic ethical perspective that integrates mind and body. Ultimately, martial arts emerge as a lived ethical practice of self-cultivation, resilience and harmony.